Assessing and Mapping the Flood Vulnerability of Krueng Baro Watershed, Aceh, Indonesia Using GIS-Based Hierarchical Criteria Analysis - Rahmi, Rahmi; Achmad, Ashfa; Yulianur, Alfiansyah; Ramli, Ichwana (Engineering, Technology & Applied Science Research, 2026)
Land Use and Land Cover (LULC) change has increasingly shaped flood vulnerability across many watersheds, including those in Indonesia. In the Krueng Baro Watershed in Aceh, the rapid conversion of permeable areas into impervious surfaces has reduced infiltration capacity, increased runoff, and intensified river discharge, thereby expanding flood-prone zones. This study aims to map and evaluate flood vulnerability by adopting an approach that accounts for greater variation in several biophysical parameters. A scoring and weighting approach was applied using 2019 LULC data and six variables: rainfall, soil type, slope gradient, river density, land use, and elevation. To strengthen the analysis, additional simulations were conducted with different variable combinations to assess model sensitivity. The results indicate that river density, elevation, and land use exert the strongest influence, with high river density, low elevation, and intensive land use closely associated with deeper and more extensive flooding. These findings underscore the urgent need for spatial planning and environmental management strategies, particularly through ecosystem restoration, periodic land-use planning reviews, and river normalization. Beyond providing technical insights, this study offers a practical framework that is adaptable to other watersheds facing similar pressures from LULC dynamics and supports policymakers in developing adaptive flood management strategies that integrate ecological perspectives into spatial planning.